Stabroek en Demerara, het ontstaan van de stadsplattegrond van Georgetown (Guyana) in de achttiende eeuw - Lex Bosman (Bulletin KNOB, 2003)
The eighteenth-century establishment of Dutch towns overseas is interesting because such town-planning matters were hardly an issue in the Netherlands itself at that time. For the then colony of Demerara (Guyana) in South America J.C. Heneman made an interesting design for a small town planned some distance upstream by the river of the same name.